مسالك الإمام الخطابي في شرح غريب الحديث من خلال كتابه "غريب الحديث - سديرة, آسيا (University of Eloued جامعة الوادي, 2018)
إن هذه الدراسة تعنى ببيان مسالك الإمام الخطابي في شرح غريب من خلال كتابه غريب الحديث ، افتتحتها بمقدمة و مقدمة تحتوي على إشكالية وقسمتها إلى ثلاثة مباحث. يتكون المبحث الأول من جزءين الجزء الأول' ترجمة الإمام الخطابي' والجزء الثاني' كتابه غريب الحديث'. بالنسبة للترجمة فقد تناولت سيرته العلمية والذاتية أما بالنسبة لكتابه' غريب الحديث' فقد بداته باسم الكتاب وسبب تأليفه ثم اتبعته طريقة عرض مواد الكتاب وأحاديثه وأقسامه. في ما يخص المبحث الثاني فقد شرحت فيه معنى علم الغريب لغة واصطلاحا بالاعتماد على كتب اللغة والحديث ثم اتبعته بأهمية علم الغريب وحركة التأليف في هذا العلم وأهم المؤلفات فيه اما المبحث الأخير الذي يعتبر محور الدراسة فقد قسمته إلى ثلاثة مطالب هي نفسها التي استعان بها الإمام الخطابي أولا استأنس بالقرآن الكريم و ثانيا بالحديث النبوي ثم ثالثا بالشعر العربي This study is concerned with the statement of the pathways of the Imam Al-Khattabi in a strange explanation through his book Ghareeb Al-Hadith, opening it with an introduction and introduction containing problematic and dividing it into three sections. The first part consists of two parts: the first part is 'the translation of the Imam al-Khattabi' and the second part 'his book is strange to talk.' As for the translation, it dealt with his biography and self-study. As for his book 'Ghareeb al-Hadith', he began with the name of the book and the reason for its authorship, followed by the presentation of the book's articles, As for the second subject, I explained the meaning of the science of the strange language and terminology based on the books of language and modern and then followed the importance of the science of the strange and the movement of authorship in this science and the most important literature in the last subject, which is the focus of the study has divided it into three demands are the same used by Imam al-Khattabi First, the Holy Quran, secondly with the Prophet's Hadith and then with the Arabic poetry
مذكرة ماستر تخصص علوم حديث
Keywords: مسالك الإمام الخطابي، غريب الحديث، شرح غريب الحديث، حركة التأليف: Strangest speech, strange speech, explain the strange modern, the movement of authorship.